Culture and inflation in Weimar Germany - Widdig, Bernd (Berkeley : University of California Press, 2001)
For many Germans the hyperinflation of 1914-1923 was one of the most decisive experiences of the 20th century. This study investigates the effects of that inflation on German culture during the Weimar Republic.
Preliminaries; Contents; List of Illustrations; List of Tables; Acknowledgments; 1. Money Matters: Culture and Inflation; 2. Flirting with Disaster; 3. Daily Explosions: Canetti's Inflation; 4. Under the Sign of Zero: Money and Inflation; 5. Uncanny Encounters: Dr. Mabuse, the Gambler; 6. Visions of Work: Hugo Stinnes and His Doubles; 7. Cultural Capital in Decline: Inflation and the Distress of Intellectuals; 8. Witches Dancing: Gender and Inflation; 9. Aftershocks: Inflation, National Socialism, and Beyond; Notes; Bibliography; Index.
Includes bibliographical references (pages 251-272) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Germany -- Social conditions -- 1918-1933.; Inflation (Finance) -- Germany -- History; Germany -- History -- 1918-1933.; Germany -- Economic policy -- 1918-1933.; German literature -- 20th century -- History and criticism; Germany -- Civilization -- 20th century; Money in literature; Antisemitism -- Germany -- History -- 20th century; Allemagne -- Conditions sociales -- 1918-1933.; Inflation -- Allemagne -- Histoire; Allemagne -- Histoire -- 1918-1933.; Allemagne -- Politique économique -- 1918-1933.; Littérature allemande -- 20e siècle -- Histoire et critique; Allemagne -- Civilisation -- 20e siècle.; Antisémitisme -- Allemagne -- Histoire -- 20e siècle.; BUSINESS & ECONOMICS -- Inflation; Antisemitism; Civilization; Economic policy; German literature; Inflation (Finance); Money in literature; Social conditions; Germany; Geschichte; Inflation; Kultur; Kunst; Deutschland; Weimarer Republik; Wirtschaft; 1900-1999; Criticism, interpretation, etc; History